Remote Work, Children's Health and the Racial Gap in Female Wages - Amairisa Kouki; Robert M. Sauer (Institute of Labor Economics (IZA), 2022)
This paper studies the racial gap in the female wage penalty to remote work. Using a temporary child health problem as a source of exogenous variation in the propensity to work from home, wage penalties reach 86 percent for black women and 77 percent for white women. Promotion bias, task re-assignment and lack of productive social interaction are the most likely mechanisms for the wage losses. The estimates provide rare evidence on the differential costs of social distancing by race and may be especially applicable when children are temporarily quarantined due to illness.
Keywords: C26; J13; J22; I19; 330; female labor supply; female earnings; race; remote work; telecommuting; flexible working arrangements; fertility; health